Price Responses to Index Additions and Deletions: A Systematic Review with Bibliometric Analysis - Goyal, Priyanka; Soni, Pooja (Gyan Management Journal, 2023)
The present study aims to systematically review the research evidence  available on the impact of additions and deletions of companies from  various stock indices on their stock prices and provide directions for  future research. This study followed the Preferred Reporting Items for  Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram  to select the final sample of 44 studies for systematic literature review  using the Scopus database. These research studies have been reviewed  subsequently to categorize, synthesize and map the extant literature using  R studio. The study found that, on average, there is an increase in share  prices of stocks being added to an index and stocks being excluded from  the index evidenced negative abnormal returns. But the existing literature  doesn’t provide conclusive evidence on whether these price effects are long  or short-term. The study guides the investors, traders and other market  participants regarding their long and short positions in the market and  also provides future research directions to academicians.
Keywords: Event study; index revisions; stock prices; index reconstitution; abnormal returns